Regulatory effects of differential dietary energy levels on spermatogenesis and sperm motility of yellow-feathered breeder cocks - Xue, Fuguang; Liu, Yifan; Lv, Ziyang; Zhang, Jian; Xiong, Shiyuan; Zha, Liqing; Liu, Zhiyu; Shu, Jingting (Frontiers in Veterinary Science, 2022)
Semen quality of breeder cocks profoundly impacted the numbers of matched layer hens and the economic benefits of the poultry industry. Adequacy and balance of poultry nutrition, especially the energy provision, critically modulated the reproductive potential of breeder cocks, however, the underlying mechanism was still unclear. Therefore, a total of 90 yellow-feathered 13-weeks old roosters with the same age in days and similar body weight (1437g±44.3g) were randomly divided into the low energy diet (LE), the moderate energy diet (ME), and the high energy diet (HE) treatments. Reproductive related phenotypic parameters included the semen quality, fertility, hatchability and the testis morphological parameters included seminiferous epithelium length (SEL), seminiferous tubule perimeter (STP), seminiferous tubule area (STA), and Johnsen score were measured to investigate the regulatory effects of different diet energy on reproductive performances. Further, spermatogenesis and sperm motility related genes which included the sry-related high mobility group box (SOX) gene family and sperm-associated antigen (SPAG) gene family, and mitochondria apoptosis related genes such as Cyt-C, Bcl-2, and Bax were measured to determine the underlying mechanism of energy on the reproductive performances. Results showed that gonadosomatic index and sperm motility in moderate energy treatment significantly increased compared with the LE. Chickens under moderate energy treatment showed a preferable testis development performance, especially a significant increment of SEL and Johnsen Score compared with the low and high energy treatments. Finally, Spermatogenesis related genes included SPAG6, SPAG16, SOX5, SOX6, and SOX13 significantly up-regulated in moderate energy treatment, likewise, the Cyt-C and Bcl-2. In summary, proper energy provision stimulated regularly energy metabolism for spermatogenesis and sperm capacitation, which finally increased semen quality and reproductive performances of breeder cocks.